Complex application of certain micronatrients in men with androgen deficiency and pathosprimes - Minukhin, A. S.; Bondarenko, V. A.; Kononenko, N. M. (Journal of Education, Health and Sport, 2018)
A complex approach was made for the deactivation of deuterine micronutrients, which include antioxidant and metabolic metabolism, in individuals with androgen deficiency and idiopathic pathospermia. It has been shown that is using the complex preparation «FEROLL» for 60 days leads to increase the parameters of the spermogram to normal values on the background of normal androgen levels of blood in these patients.